News Reading Interest and News Literacy in Senior High School Students - Jerry May B. Galamporte (Philippine Social Science Journal, 2019)
The paper looked into the news reading interest and news literacy of 310 Senior High School students. Using a descriptive, comparative, correlational design, researcher-made survey questionnaires were utilized to gather data. The study utilized mean, standard deviation, Independent Sample T-test for Means and Pearson Product Moment Coefficient of Correlation. Results revealed that the respondents' level of news reading interest as a whole and when grouped according to sex and track was average, and their level of news literacy was high.  In terms of news reading interest, there was no significant difference when they were grouped according to sex, but a significant difference was found when they were grouped according to track. Significant difference was found in the level of news literacy when they were grouped into sex and track. There is a significant relationship between news reading interest and news literacy. The findings of the study were utilized as basis for the creation of the News Literacy Instructional Module.